A note on "Existence and uniqueness of coexistence states for an elliptic system coupled in the linear part", by Hei Li-jun, Nonlinear Anal. Real World Appl. 5, 2004. (February 2022) - Girardin, Léo
Abstract: In this short paper I report on a paper published in Nonlinear Analysis: Real World Applications in 2004. There is a major mistake early in that paper which makes most of its claims false. The class of reaction–diffusion systems considered in the paper has been the object of a renewed investigation in the past few years, by myself and others, and recent discoveries provide explicit counter-examples.